Revisiting women empowerment: a retrospect on the other side of readymade garment industry - Qadir, Humayra Binte (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2016.